A framework for polyvictimization in later life. Issue 5 (20th October 2017) - Teaster, Pamela B.
ABSTRACT: This article provides a context and overview for what is known about polyvictimization in later life. Drawing from previous literature, the article includes a definition of the phenomenon, as well as theoretical constructs by which it may be understood. We place other forms of polyvictimization within the context of elder abuse, recognize frameworks for conceptualizing polyvictimization in later life, and distinguish between polyvictimization at younger ages and polyvictimization in later life. The paper concludes with implications of the framework for research, practice, and policy.